Antibacterial Efficacy of Nanoparticles of Rambutan Peel Extracts (Nephelium lappaceum L.) compared to Microparticles against Oral Bacteria - Florenly, Florenly; Wijaya, Cindy D.; Kelvin, Kelvin; Bao, Nguyen P. G.; Dung, Pham C. T. (Universitas Sam Ratulangi, 2022)
Abstract: Oral biofilm containing microorganisms is responsible for various oral infections and inflammatory diseases. Bioactive compounds found in rambutan peel extracts (Nephelium lappaceum L) has antibacterial properties. Nanoparticle sizes were known to have the greater capability as an a antimicrobial. This study aimed to compare the efficacy of rambutan peel extracts (RPEs) in micro-particles with nanoparticles against oral bacteria, i.e. Streptococcus mutans and Staphylococcus aureus. This was a laboratory experimental study with a post-test-only design conducted by using RPEs in microparticles (62.5 mg/mL and 250 mg/mL) and nanoparticles (26.5 mg/mL). The particle sizes were measured; the active compound screening was carried out with gas chromatography-mass spectrometry (GC–MS); and the antibacterial activities were tested with the disc diffusion method. The particle size distribution for RPEs with microparticles was measured at 2489 nm, whereas the nanoparticle at 7.491 nm. The GC-MS results demonstrated that both microparticles and nanoparticle RPEs contained oleic acid, hexadecanoic acid, and decanoic acid. A higher percentage of oleic acid was found in nanoparticles of RPEs. There was a significant difference between microparticles of RPEs of 62.5 mg/mL (12.83±1.532) and nanoparticles (16.25±1.529). This study demonstrated that inhibitory power increased along with the elevation of RPEs’ concentration as the number of chemi-cal components intensified. The ANOVA and post-hoc Tukey HSD test showed significant differences in the effectiveness of RPEs in nanoparticles groups compared to microparticles 62.5 mg/ml against S. mutans (p<0.05). and S. aureus (p<0.05). In conclusion, RPEs were more effective in inhibiting Staphylococcus aureus than Streptococcus mutans.Keywords: nanoparticles; rambutan peels; Nephelium lappaceum L; antibacterial activity; Streptococcus mutans; Staphylococcus aureus